A TEI P5 Manuscript Description Adaptation for Cataloguing Digitized Arabic Manuscripts - Mohammed Ourabah Soualah; Mohamed Hassoun (Journal of the Text Encoding Initiative)
It is incumbent upon libraries holding Arabic manuscripts to provide access to digitized surrogates of their holdings. Users require access both by authority list and by content. Thus, an exhaustive cataloguing method is essential. The TEI P5 Manuscript Description module is a suitable tool for manuscript cataloguing, but it lacks certain features that would allow for exhaustive description of ancient Arabic manuscripts. In this article we make several suggestions that would augment the TEI P5 Manuscript Description module allowing for a richer and more accurate description and cataloging of ancient Arabic manuscripts.